Human model of IRX5 mutations reveals key role for this transcription factor in ventricular conduction. Issue 9 (8th September 2020) - Al Sayed, Zeina R; Canac, Robin; Cimarosti, Bastien; Bonnard, Carine; Gourraud, Jean-Baptiste; Hamamy, Hanan; Kayserili, Hulya; Girardeau, Aurore; Jouni, Mariam; Jacob, Nicolas; Gaignerie, Anne; Chariau, Caroline; et al.
Abstract: Aims: Several inherited arrhythmic diseases have been linked to single gene mutations in cardiac ion channels and interacting proteins. However, the mechanisms underlying most arrhythmias, are thought to involve altered regulation of the expression of multiple effectors. In this study, we aimed to examine the role of a transcription factor (TF) belonging to the Iroquois homeobox family, IRX5, in cardiac electrical function. Methods and results: Using human cardiac tissues, transcriptomic correlative analyses between IRX5 and genes involved in cardiac electrical activity showed that in human ventricular compartment, IRX5 expression strongly correlated to the expression of major actors of cardiac conduction, including the sodium channel, Nav1.5, and Connexin 40 (Cx40). We then generated human-induced pluripotent stem cells (hiPSCs) derived from two Hamamy syndrome-affected patients carrying distinct homozygous loss-of-function mutations in IRX5 gene. Cardiomyocytes derived from these hiPSCs showed impaired cardiac gene expression programme, including misregulation in the control of Nav1.5 and Cx40 expression. In accordance with the prolonged QRS interval observed in Hamamy syndrome patients, a slower ventricular action potential depolarization due to sodium current reduction was observed on electrophysiological analyses performed on patient-derived cardiomyocytes, confirming the functional role of IRX5 in electrical conduction. Finally, a cardiac TF complex was newly identified, composed by IRX5 and GATA4, in which IRX5 potentiated GATA4-induction of SCN5A expression. Conclusion: Altogether, this work unveils a key role for IRX5 in the regulation of human ventricular depolarization and cardiac electrical conduction, providing therefore new insights into our understanding of cardiac diseases. Graphical Abstract: